A Systematic Review of Geometric Road Design Evaluation Methods with AutoCAD Civil 3D Applications: Tinjauan Sistematis Metode Evaluasi Desain Geometris Jalan dengan Aplikasi AutoCAD Civil 3D - Candra, Bangkit Yanuar Yularso; Heryadiana, Asep Dian; Prasetijo, Joewono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Geometric road design is fundamental to the development of efficient, safe, and sustainable transportation systems. In recent years, the application of digital tools, particularly AutoCAD Civil 3D, has significantly improved the accuracy and efficiency of road design processes. This systematic review investigates evaluation methods for geometric road design published between 2020 and 2025, with a focus on the use of AutoCAD Civil 3D as a primary tool. The review synthesizes findings from peer-reviewed journals, highlighting how Civil 3D has been applied in tasks such as horizontal and vertical alignment analysis, cross-section modeling, and corridor development. Results indicate that AutoCAD Civil 3D not only streamlines the design workflow but also supports better decision-making through three-dimensional visualization and real-time data integration. However, the review also identifies several limitations, including software complexity, the need for specialized training, and challenges in interoperability with other systems. Overall, this study emphasizes the critical role of AutoCAD Civil 3D in modern road design evaluation and encourages the adoption of standardized methodologies and continuous professional development to optimize its application in transportation infrastructure planning